Economic or non-economic factors: What empowers women? - Ranjula Bali Swain; Fang Yang Wallentin (Uppsala University, Department of Economics, 2008)
Microfinance programs like Self Help Group Bank linkage program (SHG), aim to empower women through provision of financial services. We investigate this further to determine whether it is the economic or the non-economic factors that have a greater impact on empowering women. Using household survey data on SHG from India, a general structural model is adopted where the latent women empowerment and its latent components (economic factors and financial confidence, managerial control, behavioural changes, education and networking, communication and political participation and awareness) are measured using observed indicators. The results show that for SHG members, economic factors, managerial control and behavioural changes are the most significant factors in empowering women.
urn:nbn:se:uu:diva-86701
Keywords: D12; D63; D91; J16; O12; O16; 330; microfinance; impact; women empowerment; Mikrofinanzierung; Selbsthilfeförderung (Entwicklungsländer); Frauen; Wirkungsanalyse; Indien